TECHNOLOGY-ENABLED ENGLISH LEARNING TRAINING FOR MTs TEACHERS IN THE WAJO DISTRICT - Yusuf Razak; Satriani Satriani; Amiruddin Amiruddin (Jurnal Abdimas Indonesia, 2021)
For the majority of students, English is a dreaded subject. Mastering English necessitates the repetition of patterns used in daily speech, as our pupils are more likely to communicate in regional languages and Indonesian. It is almost always tough for English teachers to urge their students to learn English. As a result of this occurrence, we as English lecturers are committed to giving students with learning options that allow them to enjoy learning English while being focused on the goal. We introduce technology-based English classes and educate this subject to MTs teachers around Wajo Regency, who will later serve as the students' learning relay.